Exploration of Gas-Dependent Self-Adaptive Reconstruction Behavior of Cu2O for Electrochemical CO2 Conversion to Multi-Carbon Products - Zhang, Chaoran; Gu, Yichuan; Jiang, Qu; Sheng, Ziyang; Feng, Ruohan; Wang, Sihong; Zhang, Haoyue; Xu, Qianqing; Yuan, Zijian; Song, Fang (Nano-Micro Letters, 2024)
Structural reconstruction of electrocatalysts plays a pivotal role in catalytic performances for CO2 reduction reaction (CO2RR), whereas the behavior is by far superficially understood. Here, we report that CO2 accessibility results in a universal self-adaptive structural reconstruction from Cu2O to Cu@CuxO composites, ending with feeding gas-dependent microstructures and catalytic performances. The CO2-rich atmosphere favors reconstruction for CO2RR, whereas the CO2-deficient one prefers that for hydrogen evolution reaction. With the assistance of spectroscopic analysis and theoretical calculations, we uncover a CO2-induced passivation behavior by identifying a reduction-resistant but catalytic active Cu(I)-rich amorphous layer stabilized by *CO intermediates. Additionally, we find extra CO production is indispensable for the robust production of C2H4. An inverse correlation between durability and FECO/FEC2H4 is disclosed, suggesting that the self-stabilization process involving the absorption of *CO intermediates on Cu(I) sites is essential for durable electrolysis. Guided by this insight, we design hollow Cu2O nanospheres for durable and selective CO2RR electrolysis in producing C2H4. Our work recognizes the previously overlooked passivation reconstruction and self-stabilizing behavior and highlights the critical role of the local atmosphere in modulating reconstruction and catalytic processes. Highlights: 1 We revealed a universal self-adaptive structural reconstruction from Cu2O to Cu@CuxO composites, ending with feeding gas-dependent microstructures and catalytic performances. 2 We uncovered a CO2-induced passivation behavior by identifying a reduction-resistant but catalytic active Cu(I)-rich amorphous layer. 3 We designed and fabricated hollow Cu2O nanospheres, demonstrating durable electrolysis at a partial current density of −200 mA cm−2 in producing C2H4 with an FE of up to 61% at −0.6 VRHE.